2017
DOI: 10.1104/pp.16.01605
|View full text |Cite
|
Sign up to set email alerts
|

The Sites of Evaporation within Leaves

Abstract: The sites of evaporation within leaves are unknown, but they have drawn attention for decades due to their perceived implications for many factors, including patterns of leaf isotopic enrichment, the maintenance of mesophyll water status, stomatal regulation, and the interpretation of measured stomatal and leaf hydraulic conductances. We used a spatially explicit model of coupled water and heat transport outside the xylem, MOFLO 2.0, to map the distribution of net evaporation across leaf tissues in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
106
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 57 publications
3
106
1
Order By: Relevance
“…The second model posits evaporation from the guard cells directly, leading to their water loss and stomatal closure. However, a growing body of evidence indicates that the bulk of the evaporation within the leaf occurs well away from the guard cells, dominated instead by evaporation from the vascular tissue, nearby mesophyll and pavement cells (Pieruschka et al, 2010;Rockwell et al, 2014;Buckley et al, 2017). These studies imply that water in the guard cell is maintained primarily by equilibration with water in the vapor phase within the adjacent substomatal cavity and the stomatal pore rather than by liquid flow through the cell wall and neighboring cells.…”
Section: Rationale For the Modeling Approachmentioning
confidence: 96%
See 3 more Smart Citations
“…The second model posits evaporation from the guard cells directly, leading to their water loss and stomatal closure. However, a growing body of evidence indicates that the bulk of the evaporation within the leaf occurs well away from the guard cells, dominated instead by evaporation from the vascular tissue, nearby mesophyll and pavement cells (Pieruschka et al, 2010;Rockwell et al, 2014;Buckley et al, 2017). These studies imply that water in the guard cell is maintained primarily by equilibration with water in the vapor phase within the adjacent substomatal cavity and the stomatal pore rather than by liquid flow through the cell wall and neighboring cells.…”
Section: Rationale For the Modeling Approachmentioning
confidence: 96%
“…Similarly, we define this exchange to take place with the potential of liquid water averaged over the guard cell surface. Beyond exchange with the guard cell, the p concept does not specify the tissues from which the bulk of evaporation occurs and accommodates evaporation from the mesophyll as well as from the inner surface of the epidermis (Buckley et al, 2017). Since the conductivity for liquid water to the stomatal pore will be much lower than that for water vapor within the leaf air space, cells at different points in the leaf along the transpiration path will exchange with different partial pressures of water in the vapor phase.…”
Section: Connecting the Vapor Phase With Guard Cell Watermentioning
confidence: 99%
See 2 more Smart Citations
“…In these circumstances, the assumption leads to an overestimation of the VPD across the stomatal pore and, hence, an underestimation of the true g s (Buckley et al, 2017), potentially accounting for the apparent drop in g s with VPD steps observed by Merilo et al (2018). To eliminate this explanation, alternative porometry techniques (Farquhar and Raschke, 1978;Pantin et al, 2013) are needed to assess g s independent of evapotranspiration.…”
mentioning
confidence: 99%